Web-Age Information Management WAIM 2012 International Workshops: GDMM, IWSN, MDSP, USDM, and XMLDM Harbin, China, August 18-20, 2012 Proceedings - Bao, Zhifeng; Gao, Yunjun; Gu, Yu.; Guo, Longjiang; Li, Yingshu; Lu, Jiaheng; Ren, Zujie; Wang, Chaokun; Zhang, Xiao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed proceedings of five workshops of the 13th International Conference on Web-Age Information Management, WAIM 2012, held in Harbin, China, in August 2012. The 34 revised full papers are organized in topical sections on the five following workshops: the First International Workshop on Graph Data Management and Mining (GDMM 2012), the Second International Wireless Sensor Networks Workshop (IWSN 2012), the First International Workshop on Massive Data Storage and Processing (MDSP 2012), the Third International Workshop on Unstructured Data Management (USDM 2012); the 4th International Workshop on XML Data Management (XMLDM 2012).
The First International Workshop on Graph Data Management and Mining (GDMM 2012) -- the Second International Wireless Sensor Networks Workshop (IWSN 2012) -- the First International Workshop on Massive Data Storage and Processing (MDSP 2012) -- the Third International Workshop on Unstructured Data Management (USDM 2012) -- the 4th International Workshop on XML Data Management (XMLDM 2012).
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Database management; Data mining; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Database Management; Computer Communication Networks; Data Structures